MIXED CONVECTION IN A SINGLE-WALLED CARBON NANOTUBE-WATER NANOFLUID FILLED PARTIALLY HEATED TRIANGULAR LID-DRIVEN CAVITY HAVING AN ELASTIC BOTTOM WALL - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Yildiz Technical Univ, 2020)
In this study, mixed convection of nanofluid filled triangular cavity with a partial heater and having an elastic bottom wall is analyzed with finite element method. Left vertical wall is partially heated while the inclined wall is kept at constant lower temperature. The bottom wall is flexible and inclined wall is moving at constant speed. Influences of Richardson number, elastic modulus of flexible wall, solid nanoparticle volume fraction on the convective heat transfer characteristics are analyzed. It was observed that, lower values of Richardson number, elastic modulus of the flexible wall and higher values of nano-particle volume fraction resulted in higher local and average heat transfer enhancements. Average heat transfer enhanced significantly when solid particle volume fraction of nanoparticle was increased. Enhancements up to 121% were obtained at solid volume fraction of 0.04 as compared to pure water at Richardson number of 1. Effects of elastic modulus of the bottom wall were found to be marginal and at Ri=1, enhancements up to 2% were achieved by using a more flexible wall.
Keywords: Carbon Nanotube; Nanofluid; Flexible Wall; Mixed Convection; Simulation